Conversion to belatacept within 1‐year of renal transplantation in a diverse cohort including patients with donor‐specific antibodies. Issue 4 (13th March 2020) - Santeusanio, Andrew D.; Bhansali, Arjun; Weinberg, Alan; Shapiro, Ron; Delaney, Veronica; Florman, Sander; De Boccardo, Graciela
Abstract: Early conversion from a calcineurin inhibitor to belatacept has the potential to improve long‐term renal allograft function; however, there remains limited experience with this strategy among African Americans and patients with preformed donor‐specific antibodies (DSA). To examine these subgroups, we performed a single‐center review of kidney transplant recipients converted to belatacept within 1‐year of transplant between 01/2011 and 10/2017. All patients received lymphocyte‐depleting induction with maintenance tacrolimus and mycophenolate +/− corticosteroids. Patients were switched to belatacept for clinical indication and followed from date of conversion until allograft failure or study conclusion. The primary endpoint at 1‐year was a composite of allograft loss, biopsy proven rejection, de novo DSA formation, proteinuria, and declining renal function. Thirty‐two patients were included in the review. The majority were African American, and 28.1% had DSA at transplant. Patient and allograft survival at 1‐year was 96.9% and 93.8%, respectively, and estimated glomerular filtration rate improved from 41.9 to 58.4 mL/min. No African Americans or patients with pretreatment DSA developed rejection or allograft failure within 1‐year. The only clinical variable correlated with suboptimal allograft function was baseline weight ≥80 kg (OR = 6.2; 95% CI, 1.2‐32.3). Early conversion to belatacept appears safe for select patients with DSA and African Americans receiving lymphocyte‐depleting induction.